Women in print : essays on the print culture of American women from the nineteenth and twentieth centuries - Danky, James Philip, 1947-; Wiegand, Wayne A., 1946- (Print culture history in modern America., 2006)
Women readers, editors, librarians, authors, journalists, booksellers, and others are the subjects in this stimulating new collection on modern print culture. The essays feature women like Marie Mason Potts, editor of Smoke Signals, a mid-twentieth century periodical of the Federated Indians of California; Lois Waisbrooker, publisher of books and journals on female sexuality and women's rights in the decades after the Civil War; and Elizabeth Jordan, author of two novels and editor of Harper's Bazaar from 1900 to 1913. The volume presents a complex and engaging picture of print culture and of the forces that affected women's lives in the nineteenth and twentieth centuries.--Publisher description.